Effects of different basal cell culture media upon the osteogenic response of hMSCs evaluated by 99mTc-HDP labeling - Großner, Tobias; Haberkorn, Uwe; Hofmann, Jakob; Gotterbarm, Tobias (International journal of molecular sciences, 2022)
The osteogenic differentiation of mesenchymal stem cells is now a standard procedure in modern bone tissue engineering. As this is a promising field for future clinical applications, many cell culture media exist to promote osteogenic differentiation. Prior to differentiation, cells must be expanded to obtain sufficient numbers for experiments. Little evidence is available regarding the optimal media combination for expansion and differentiation to maximize the osteogenic response. Therefore, human BM-MSCs (n = 6) were expanded in parallel in DMEM (Dulbecco’s Modified Eagle Medium) LG (Low Glucose) and α-MEM (Minimum Essential Media alpha-modification), followed by simultaneous monolayer differentiation toward the osteogenic lineage in: 1. DMEM LG (Low Glucose), 2. DMEM HG (High Glucose), 3. α-MEM, 4. “Bernese medium”, and 5. “Verfaillie medium”, with a corresponding negative control (total 20 groups). As a marker for osteogenic differentiation, hydroxyapatite was accessed using radioactive 99mTc-HDP labeling and quantitative alizarin red staining. The results indicate that all media except “Bernese medium” are suitable for osteogenic differentiation, while there was evidence that DMEM LG is partly superior when used for expansion and differentiation of BM-hMSCs. Using “Verfaillie medium” after DMEM LG expansion led to the highest grade of osteogenic differentiation. Nevertheless, the difference was not significant. Therefore, we recommend using DMEM LG for robust osteogenic differentiation, as it is highly suitable for that purpose, economical compared to other media, and requires little preparation time.
Im Titel ist "99m" bei "Tc-HDP" hochgestellt
Gesehen am 06.07.2022